Assessment of the Physicochemical and Antioxidant Profile of Dried Goji Berries (Lycium barbarum) - Ağagündüz, Duygu; Köseler Beyaz, Esra; Duman, Sinem (Progress in Nutrition, 2022)
This study aimed to determine the physicochemical properties and antioxidant capacity of the dry goji berry fruit. Sun-dried goji berry fruits (Lycium barbarum) harvested in Manisa-Turkey, and sold in the local market were collected. Total phenolic content (TPC) was determined by the Folin-Ciocalteu method, and the ferric reducing ability of plasma (FRAP) assay was utilized for antioxidant activity. 2,6 dichlorophenolindophenol spectrophotometric method was used in the ascorbic acid analysis. Mineral contents and the percentage contribution to the recommended daily allowance (RDA) of dry fruits were determined. TPC values of samples were 207.2±1.51 mg GAE/100 g and their antioxidant activities were found to be 32.6±1.82 µmol TE/g.The fruit samples of 100 gram included 31.0±1.62 mg of ascorbic acid. Mineral contents and the percentage contribution to the RDA of 100 grams of dry goji berry fruits were as follows: calcium:49.0 mg (5.0%), phosphorus:370.0 mg (67.2%), sodium:1.32 mg (94.2%), potassium: 193.0 mg (>4000%), magnesium:120.0 mg (36.9%), iron:0.04 mg (0.3%), copper: 0.01 mg (0.7%) and manganese:0.008 mg (0.26%), The results of the present study suggest that goji berry cultivated in not only Asia but also Turkey certainly deserve further investigation because it contains a significant amount of vitamin C and some essential minerals, and with its phenolic content/antioxidant capacity even if it is traditionally sun-dried.